Human Salmonella Typhi exposure generates differential multifunctional cross-reactive T-cell memory responses against Salmonella Paratyphi and invasive nontyphoidal Salmonella - Rapaka, RR; Wahid, R; Fresnay, S; Booth, JS; Darton, TC; Jones, C; Waddington, CS; Levine, MM; Pollard, AJ; Sztein, MB (Wiley Open Access, 2020)
Objective: There are no vaccines for most of the major invasive Salmonella strains causing severe infection in humans. We evaluated the specificity of adaptive T memory cell responses generated after Salmonella Typhi exposure in humans against other major invasive Salmonella strains sharing capacity for dissemination. Methods: T memory cells from eleven volunteers who underwent controlled oral challenge with wtS. Typhi were characterised by flow cytometry for cross-reactive cellular cytokine/chemokine effector responses or evidence of degranulation upon stimulation with autologous B-lymphoblastoid cells infected with either S. Typhi, Salmonella Paratyphi A (PA), S. Paratyphi B (PB) or an invasive nontyphoidal Salmonella strain of the S. Typhimurium serovar (iNTSTy). Results: Blood T-cell effector memory (TEM) responses after exposure to S. Typhi in humans evolve late, peaking weeks after infection in most volunteers. Induced multifunctional CD4+ Th1 and CD8+ TEM cells elicited after S. Typhi challenge were cross-reactive with PA, PB and iNTSTy. The magnitude of multifunctional CD4+ TEM cell responses to S. Typhi correlated with induction of cross-reactive multifunctional CD8+ TEM cells against PA, PB and iNTSTy. Highly multifunctional subsets and T central memory and T effector memory cells that re-express CD45 (TEMRA) demonstrated less heterologous T-cell cross-reactivity, and multifunctional Th17 elicited after S. Typhi challenge was not cross-reactive against other invasive Salmonella. Conclusion: Gaps in cross-reactive immune effector functions in human T-cell memory compartments were highly dependent on invasive Salmonella strain, underscoring the importance of strain-dependent vaccination in the design of T-cell-based vaccines for invasive Salmonella.